Dynamic competence in the opinion of the machinery sector experts - from theory to management practice = Kompetencje dynamiczne w opinii ekspertów sektora maszynowego - od teorii do praktyki zarządzania - Nogalski, Bogdan; Niewiadomski, Przemysław; Szpitter, Agnieszka A. (Zielona Góra: Faculty of Economics and Management Press)
The main objective of this paper is an attempt to reply to the question: how is the concept of dynamic competence understood by representatives of the manufacturing companies operating in the Polish agricultural machinery sector? Within the theoretical and design measures, a method of reconstruction and interpretation of literature implying the discussion in a group of intentionally selected experts operating in the examined sector will be used; as a result of the creative discussion, the key designates of was considered appropriate to determine the hierarchy of their importance. The task of deliberately selected respondents will be to make a choice as to which of the suggested dimensions of the dynamic competence best reflects the sense of this concept.
Keywords: kompetencje dynamiczne; zasoby materialne; zasoby niematerialne; zdolności dynamiczne; dynamic competencies; tangible resources; intangible resources; dynamic capabilities